(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The contribution takes stock of the intense legislative activity occurred in the last year in Russia. This has taken place against the background of a “frozen” political regime which is deeply concerned about the activity of “non-systemic” opposition and “foreign agents”, and increasingly aggressive in international relations.